2022
DOI: 10.3390/su142114493
|View full text |Cite
|
Sign up to set email alerts
|

The Effects and Vertical Bearing Capacity of Two Jacked Model Piles in Sand

Abstract: The effects and vertical bearing capacity of two jacked piles in sand are still not well understood, and the mechanism of the adjacent pile’s uplift caused by the jacking pile in a double pile system is especially unclear, but these facets are important to the stability of the jacked pile. In this paper, a series of tests is performed on jacked model piles in sand, where in the influences of the pile length and the driving pile’s speed on the effects and vertical bearing capacity of two jacked piles were studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Yalcin et al [5,6] studied the bearing performance of flexible piles and small group piles under eccentric and inclined loads and noted that the ultimate bearing capacity of piles depends on the eccentricity and inclination of loads, as well as the ratio of the upper layer thickness to the pile burying depth. Wang et al [7] studied the bearing capacity of double piles under static pressure in sandy soil foundations through laboratory model tests and reported that the bearing capacity of static piles was mainly affected by the pile length and static pressure velocity, and the radial stress of piles under different pile lengths increased nonlinearly with depth and gradually converged to the passive earth pressure. Through field tests and model tests, Yang et al and Gaaver [8,9] analyzed the influencing factors including pile burying depth, soil relative density, pile spacing, and pile group layout and found that the bearing capacity of a single pile mainly depended on the pile length-diameter ratio and soil properties, and that the pulling efficiency of small-spacing pile groups decreased with the increasing number of piles in the group.…”
Section: Introductionmentioning
confidence: 99%
“…Yalcin et al [5,6] studied the bearing performance of flexible piles and small group piles under eccentric and inclined loads and noted that the ultimate bearing capacity of piles depends on the eccentricity and inclination of loads, as well as the ratio of the upper layer thickness to the pile burying depth. Wang et al [7] studied the bearing capacity of double piles under static pressure in sandy soil foundations through laboratory model tests and reported that the bearing capacity of static piles was mainly affected by the pile length and static pressure velocity, and the radial stress of piles under different pile lengths increased nonlinearly with depth and gradually converged to the passive earth pressure. Through field tests and model tests, Yang et al and Gaaver [8,9] analyzed the influencing factors including pile burying depth, soil relative density, pile spacing, and pile group layout and found that the bearing capacity of a single pile mainly depended on the pile length-diameter ratio and soil properties, and that the pulling efficiency of small-spacing pile groups decreased with the increasing number of piles in the group.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the influence of the cementation degree, Houlsby et al [34] proposed a functional relationship between the ratio of the cemented layer thickness to the pile diameter and the ultimate bearing capacity. Wang et al [35], using a model test of jacked piles, pointed out that the jacking pile pressure increases nonlinearly with the increase in pile length, in which the radial stress of the piles gradually converges with passive Earth pressure with the increase in the pile length. By analyzing the datasets of over 37 real projects on super-large and long piles, Thien et al [36] pointed out that pile length has a certain influence on the pile tip resistance, and they are positively correlated.…”
Section: Introductionmentioning
confidence: 99%